Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2002
DOI: 10.1177/0883911502017005557
|View full text |Cite
|
Sign up to set email alerts
|

N-(2-Hydroxypropyl)methacrylamide Copolymer-9-Aminocamptothecin Conjugate: Colon-Specific Drug Delivery in Rats

Abstract: An N-(2-hydroxypropyl)methacrylamide (HPMA) copolymer conjugate containing 9-aminocamptothecin (9-AC) bound via a spacer containing an aromatic azo bond and leucylalanine (P-Azo-Leu-Ala-9-AC) was synthesized. The in vivo pharmacokinetic profile after oral administration was examined in rats and compared to free 9-AC. The aromatic azo bond of P-Azo-Leu-Ala-9-AC was stable in stomach and small intestine; the delivery of a large amount of intact conjugate to the colon was achieved. In the colon, the azoreductase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…However, subsequent cleavage of drug-containing fragment by peptidase was found to be slow, as only around 36.6% of 9-AC was released 24 h after incubation in rat cecal contents [31]. And around 1.43 nmol/g of 9-AC was detected in luminal content of the colon 12 h after oral administration [32]. In order to efficiently release 9-AC, a spacer containing 4-aminobenzylcarbamate group was inserted between an aromatic azo bond and the drug.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, subsequent cleavage of drug-containing fragment by peptidase was found to be slow, as only around 36.6% of 9-AC was released 24 h after incubation in rat cecal contents [31]. And around 1.43 nmol/g of 9-AC was detected in luminal content of the colon 12 h after oral administration [32]. In order to efficiently release 9-AC, a spacer containing 4-aminobenzylcarbamate group was inserted between an aromatic azo bond and the drug.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, an HPMA copolymer conjugate was designed for colon-specific delivery of 9-AC, which was bound via spacers containing peptide and aromatic azo bonds [31]. In vitro and in vivo [32] studies indicated that after entering the colon, the aromatic azo bond was cleaved first by azoreductase activities, followed by peptidase-catalyzed cleavage of the peptide bond in the drug derivative to generate free drug. However, subsequent cleavage of drug-containing fragment by peptidase was found to be slow, as only around 36.6% of 9-AC was released 24 h after incubation in rat cecal contents [31].…”
Section: Discussionmentioning
confidence: 99%
“…First, we attached 9-AC to HPMA copolymers through a spacer containing an aromatic azo bond and amino acid residues [134,135]. It was shown that the aromatic azo bond was cleaved first in vitro [134] and in vivo [135], followed by peptidase-catalyzed cleavage of the amino acid (dipeptide) drug derivative resulting in the release of free 9-AC. However, the cleavage of the peptide drug derivative was not fast enough to achieve high concentrations of free 9-AC in the colon.…”
Section: Hpma Copolymer–drug Conjugatesmentioning
confidence: 99%
“…tures (linear, cross-linked and branched) for the design of controlled drug delivery systems [1][2][3][4][5][6][7]. Considerable interest has been shown for dendrimers as delivery systems of bioactive agents.…”
Section: Introduction P Olymers Have Been Used In Various Macromolecumentioning
confidence: 99%